Imagining Experiencing an Event in the Future Inflates Certainty That It Occurred in the Past. (September 2019) - Calvillo, Dustin P.; Flores, Andrea N.; Lara, Paul M.; Hawkins, Whitney C.; Boman, Larry D.; Smelter, Thomas J.
Imagination inflation occurs when participants increase their certainty that they have experienced an event after they imagine the event occurring. Two experiments (with a total of 291 participants) examined the effects of imagining events in the future on participants' certainty they had experienced those events in the past. Participants rated their certainty in having experienced events and then imagined experiencing some of those events either in the future or in the past. One or two weeks later, participants completed certainty ratings a second time and completed some individual difference measures. In both imagination conditions (future and past), certainty ratings increased more for imagined events than for control events. Autobiographical memory specificity and self-concept clarity did not significantly predict this effect. These findings suggest that imagining events in the future makes people more certain that they have happened in the past.